Pengaruh Locus Of Control Dan Perilaku Kepemimpinan Situasional Terhadap Kepuasan Kerja Dengan Prestasi Kerja Sebagi Variabel Intervening (Studi Kasus Pada Pt.Kencana Sawit Indonesia - Neni Sri Wahyuni Nengsi; Meri Andani; Vicky Brama Kumbara (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study aims to prove the effect of locus of control and situational leadership behavior on employee performance through job satisfaction. This study uses a quantitative approach that focuses on hypothesis testing. The independent variable is locus of control, situational leadership behavior, while the dependent variable is job satisfaction and job performance. The data collection procedure in this study was carried out using a questionnaire. The respondents were 70 employees at PT. Kencana Sawit Indonesia. Data analysis techniques to test research hypotheses were carried out using SPSS. Based on testing, conclusions; (1) the results obtained by partial locus of control have a positive and significant effect on job satisfaction, where the locus of control coefficient value is 0.723 with a small significant level of (0.000 <0.005). Means that locus of control increases, job satisfaction increases.;(2 ) the results obtained that situational leadership behavior partially has a positive effect on job satisfaction, meaning that situational leadership behavior increases, job satisfaction increases.; (3) results prove that locus of control increases, work performance increases.; (4) results proves situational leadership behavior increases, so work performance increases,; (5) results prove job satisfaction increases, work performance increases,; (6) results prove job satisfaction does not mediate locus of control on work performance,; (7) job satisfaction results do not mediate situational leadership behavior on work performance .